Implementasi Muatan Lokal Aswaja Dalam Membentuk Karakter Peserta Didik - Hasan Hariri; Ahmad Sukandar; Asep A Fathurohman (Peneliti.net, 2022)
Moral and ethical values ​​are needed in our country, so the implementation of local content education related to the character of students is able to build a nation of character. This study aims to explain how the implementation of Aswaja's local content in shaping the character of students at Madrasah Aliyah NU Indramayu. The method used in this study uses a qualitative descriptive method with the type of case study by describing how the process of implementing learning at Madrasah Aliyah NU Indramayu from beginning to end. The data collection technique in this study was carried out in three steps, namely observation, documentation study and interviews. The results of the study show: 1) Aswaja local content learning planning at MA NU Indaramayu by setting subjects, assigning tutors, determining funding sources and learning resources, 2) Aswaja local content learning implementation includes, reviewing the syllabus, making learning implementation plans, preparing assessment 3) Evaluation of local content learning Aswaja includes, evaluation of local content programs, evaluation of local content results. However, in the course of the strategy applied by the madrasah principal in learning Aswaja local content has not run optimally because there are still frequent changes of tutors for Aswaja local content subjects, as well as the teacher's ability to design and implement learning tools. Thus, it is very necessary to do research in the formation of the character of students through the local content of Aswaja.